New Insights Into Monogenic Causes of Osteoporosis - Mäkitie, Riikka E.; Costantini, Alice; Kämpe, Anders; Alm, Jessica J.; Mäkitie, Outi (Frontiers in Endocrinology, 2019)
Osteoporosis, characterized by deteriorated bone microarchitecture and low bone mineral density, is a chronic skeletal disease with high worldwide prevalence. Osteoporosis related to aging is the most common form and causes significant morbidity and mortality. Rare, monogenic forms of osteoporosis have their onset usually in childhood or young adulthood and have specific phenotypic features and clinical course depending on the underlying cause. The most common form is osteogenesis imperfecta linked to mutations in COL1A1 and COL1A2, the two genes encoding type I¬ collagen. However, in the past years, remarkable advancements in bone research have expanded our understanding of the intricacies behind bone metabolism and identified novel molecular mechanisms contributing to skeletal health and disease. Especially high-throughput sequencing techniques have made family-based studies an efficient way to identify single genes causative of rare monogenic forms of osteoporosis and these have yielded several novel genes that encode proteins partaking in type I collagen modification or regulating bone cell function directly. New forms of monogenic osteoporosis, such as autosomal dominant osteoporosis caused by WNT1 mutations or X-linked osteoporosis due to PLS3 mutations, have revealed previously unidentified bone-regulating proteins and clarified specific roles of bone cells, expanded our understanding of possible inheritance mechanisms and paces of disease progression, and highlighted the potential of monogenic bone diseases to extend beyond the skeletal tissue. The novel gene discoveries have introduced new challenges to the classification and diagnosis of monogenic osteoporosis, but also provided promising new molecular targets for development of pharmacotherapies. In this article we give an overview of the recent discoveries in the area of monogenic forms of osteoporosis, describing the key cellular mechanisms leading to skeletal fragility, the major recent research findings and the essential challenges and avenues in future diagnostics and treatments.